Rock crevices determine woody and herbaceous plant cover in the karst critical zone - Liu, Hongyan; Jiang, Zihan; Dai, Jingxi; Wu, Xiuchen; Jian, Peng; Hongya, Wang; Jereon, Meersmans; Green, Sophie M.; Quine, Timothy (Springer, 2019)
The study of the critical zones (CZs) of the Earth link the composition and function of aboveground vegetation with the characteristics of the rock layers, providing a new way to study how the unique rock and soil conditions in karst regions affect the aboveground vegetation. Based on survey results of the rocks, soils and vegetation in the dolomite and limestone distribution areas in the karst area of central Guizhou, it was found that woody plant cover increases linearly with the number of cracks with a width of more than 1 mm, while the cover of herbaceous plants shows the opposite trend (p<0.01). The dolomite distribution area is characterized by undeveloped crevices, and the thickness of the soil layer is generally less than 20 cm, which is suitable for the distribution of herbaceous plants with shallow roots. Due to the development of crevices in the limestone distribution area, the soil is deeply distributed through the crevices for the deep roots of trees, which leads to a diversified species composition and a complicated structure in the aboveground vegetation. Based on moderate resolution imaging spectroradiometer (MODIS) remote sensing data from 2001 to 2010, the normalized differentiated vegetation index (NDVI) and annual net primary productivity (NPP) results for each phase of a 16-day interval further indicate that the NDVI of the limestone distribution area is significantly higher than that in the dolomite distribution area, but the average annual NPP is the opposite. The results of this paper indicate that in karst CZs, the lithology determines the structure and distribution of the soil, which further determines the cover of woody and herbaceous plants in the aboveground vegetation. Although the amount of soil in the limestone area may be less than that in the dolomite area, the developed crevice structure is more suitable for the growth of trees with deep roots, and the vegetation activity is strong. At present, the treatment of rocky desertification in karst regions needs to fully consider the rock-soilvegetation- air interactions in karst CZs and propose vegetation restoration measures suitable for different lithologies.
Keywords: Vegetation composition; Vegetation productivity; Dolomite; Limestone; Karst critical zone